Nice Girls like Us: Confronting White Liberalism in Teacher Education and Ourselves - Kristen L. White; Sophie Degener; Amy Tondreau; Wendy Gardiner; Tierney B. Hinman; Tess M. Dussling; Elizabeth Y. Stevens; Nance S. Wilson (MDPI AG, 2024)
Niceness includes behaviors such as avoiding conflict or controversial topics, being submissive and people-pleasing, performing teaching as "love" in uncritical ways, accepting deficit perspectives, and upholding patriarchal structures. In the spirit of Niceness, white female teachers often avoid the work of challenging inequitable systems because doing so leaves them vulnerable to being seen as "not nice" or troublemakers. In this article, we interrogate how "niceness" produces and perpetuates inequalities in schooling. In particular, we argue that we, a group of eight white female teacher educators from across the United States, are in positions of leadership, capable of perpetuating or disrupting "niceness" in our pre-service courses. Drawing on scholarship on niceness, femininity, and critical whiteness, we examine our complicity in acts of oppression and how we work to identify and unlearn institutional norms to teach for justice and equity. We share vulnerable moments when we upheld niceness. In doing so, we aim to reveal and explore how socialization into niceness enables our silence, inaction, and misguided action.